Physiology and Metabolism Alterations in Flavonoid Accumulation During Buckwheat (Fagopyrum esculentum Moench.) Sprouting - Meixia Hu; Jia Yang; Jing Zhang; Weiming Fang; Yongqi Yin (Plants)
In this research, we investigated the physiological modifications, flavonoid metabolism, and antioxidant systems of two buckwheat (Fagopyrum esculentum Moench.) cultivars, Pintian and Suqiao, during germination. The results demonstrated an initial increase followed by a subsequent decline in the flavonoid content of the buckwheat sprouts throughout germination. On the third day of germination, the highest flavonoid concentrations were observed, with the Pintian and Suqiao varieties reaching 996.75 and 833.98 μg/g fresh weight, respectively. Both the activity and relative gene expression level of the flavonoid metabolizing enzyme showed a significant rise in 3-day-old buckwheat sprouts, which was strongly correlated with the flavonoid content. The correlation analysis revealed that the buckwheat sprouts accumulated flavonoids by enhancing the activities and gene expression levels of flavonoid synthases. The antioxidant capacity and the activities and gene expression profiles of the antioxidant enzymes in both buckwheat cultivars notably increased after three days of germination. The correlation analysis indicated a significant positive link between antioxidant capacity and the activity and gene expression levels of the antioxidant enzymes, flavonoid content, and total phenol content. This research demonstrated that germination treatment can significantly boost the accumulation of flavonoids and total phenols, thereby enhancing the antioxidant properties of buckwheat sprouts, despite variations among different buckwheat varieties.